Pengaruh Sumber Nitrogen yang Berbeda dalam Medium Murashige dan Skoog (MS, 1962) terhadap Produksi Senesionin pada Kultur â€œCompact Globular Structureâ€ Crotalaria anagyroides H.B.K - Surakusumah, Wahyu (Jurnal Pengajaran MIPA, 2002)
An Experiment on the effect of different nitrogen source in Murashige and Skoog media (MS, 1962) on senesionin production of compact globular structure of Crotalaria anagyroides has been performed. CGS culture was obtained from callus culture on liquid MS media with 5.10-5 M NAA and 10-6 M kinetin. The CGS was transfered into media with different nitrogen source: MS A (amonium+nitrat), MS B (nitrat) and MS C (amonium). Qualitatif data showed that senesionin could be detected in the CGS exstract by appearence of spot (Rf=0,78). The quantitative data showed that MS C was the best media to produce 4623 mg/DW senesionin on 30th day.